Eugène Piot e L’Italie monumentale (1851-1853). La fotografia fra documento ed égotisme - Serena, Tiziana (Rivista di studi di fotografia. Journal of Studies in Photography, 2015)
Eugène Piot’s album, L’Italie monumentale (1851-1853), was a true novelty in the age of French calotype. This article sets out by exploring the Italian trip Piot undertook with Gautier in 1850 and the parallel ways in which they described the country. In the second part, Piot’s own project is reconsidered: focusing on the materiality of an unpublished body of photographs, it is argued that Piot’s visual models were often shaped less by the strictures of the document than by the subjective gaze of the égotiste.